2020
DOI: 10.16993/dfl.145
|View full text |Cite
|
Sign up to set email alerts
|

Meanings Made in Students’ Multimodal Digital Stories: Resources, Popular Culture, and Values

Abstract: The young generation are both consumers and producers of digital multimodal texts and can thus be seen as cocreators of the culture and the contexts that they are part of. Learning more about how students create multimodal texts and what students' texts are about can extend the understanding of contemporary meaning making. This study examines 23 Swedish fifth-grade students' multimodal digital stories in a school context. The aim of this research was to understand the meaning that the students made in their di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It also encourages them "to understand the multimodal organization of social relations through the design of communicative resources, including linguistic meaning, visual meaning, audio meaning, and gestural and spatial meaning" (Jewitt, 2008, p. 252). Dahlström and Damber (2020) demonstrate how the notion of design can help students make sense of multimodal signs. They conducted a study on 23 Swedish fifth-grade students.…”
Section: Designing Multimodal Textsmentioning
confidence: 97%
See 1 more Smart Citation
“…It also encourages them "to understand the multimodal organization of social relations through the design of communicative resources, including linguistic meaning, visual meaning, audio meaning, and gestural and spatial meaning" (Jewitt, 2008, p. 252). Dahlström and Damber (2020) demonstrate how the notion of design can help students make sense of multimodal signs. They conducted a study on 23 Swedish fifth-grade students.…”
Section: Designing Multimodal Textsmentioning
confidence: 97%
“…The notion of design is an active and dynamic process central to communication (Cope & Kalantzis, 2000;Dahlström & Damber, 2020;Husbye & Vander Zanden, 2015;Jewitt, 2008). Design enables students to realize their interests as sign makers.…”
Section: Designing Multimodal Textsmentioning
confidence: 99%
“…Young children of today create multimodal texts using digital tools both in and out of school. Previous research, focusing on the characteristics of pupil-created texts, has shown that, when allowed to do so, pupils draw on their out-of-school experiences with digital tools, for instance when choosing images for their texts [29,30]. In classrooms where the function of digital texts has been explicit, studies indicate that the pupils have a high level of engagement [31,32] and use each other as resources during digital text work [32,33].…”
Section: Young Children's Multimodal Text Creation With Digital Toolsmentioning
confidence: 99%
“…Additional advantages of these stories over traditional storytelling comprise the option of including emotional and affective content through enhanced creativity and the freedom to use one's imagination, involve personal motivation, and offer opportunities for collaboration (Fleer, 2018;Lambert, 2010;Robin, 2008;Yocom et al, 2020). Further benefits identified in the literature include the user's development of personal and professional identity (Fleer, 2018;Kim & Li, 2020), the enhancement of academic skills (Marais, 2021), such as digital searching or oral and writing, and its service as a transformative tool for a variety of contexts (Dahlström & Damber, 2020;Kearney, 2011). Digital stories are often interdisciplinary and participatory (Robin, 2008) and have the potential to be a catalyst for great power and personal growth (Kim & Li, 2020).…”
Section: Digital Storiesmentioning
confidence: 99%